DOMESTIKASI PERAN SUAMI DALAM KELUARGA - Muassomah, Muassomah (EGALITA, 2009)
The fundamental difference between men and women is seen in terms ofÂ  biology and anatomy. Viewed from the aspect of biological male has advantages compared with women. Men have a sturdy and strong muscle, while women are more delicate. Anatomically, men do not have a uterus for pregnancy, while women have a uterus so that it is possible to conceive and bear children. With the difference that the role of men and women also differ. Some argue that the role of men is to earn a living for his family, while the task of women is pregnant, giving birth and raising children, as well as housewives. But this role is changing. The factors that cause changes in the role of the husbandâ€™s public role to the domestic role is due to economic.Keywords: Domestik, Peran suami, Keluarga